Mathematical Formulation to Differentiate between Naturally Occurred and Artificially Added Formaldehyde in the Ice Stored of Lizardfish (Saurida tumbil) - Barokah, Giri Rohmad; Anissah, Umi; Januar, Hedi Indra; Ariyani, Farida (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
The practice of formaldehyde abuse as a food preservative, especially in fishery products, is commonly occurred. However, the differentiation of the formaldehyde origin in fish is difficult to be performed. Meanwhile, physical observation is not sufficient to determine the additional formaldehyde in fishery products. This study aimed to formulate a quantitative method to detect the origin of formaldehyde in fish. The formulation was developed based on the differences in some chemical properties (Formaldehyde (FA), Trimethylamine (TMA) and Trimethylamine oxide (TMAO) of fish treated with and without formaldehyde addition. The fish used as samples were beloso fish/lizardfish (Saurida tumbil). Fish were prepared with and without the addition of formaldehyde and then stored in ice for 21 days. The content of FA, TMA, and TMAO of gill and flesh during storage were analyzed every 3 days to determine the difference in the trend of distribution patterns of two fish treatments. The data were statistically processed to produce two mathematical formulas to identify the origin of formaldehyde. The results reveal that detection of the origin of formaldehyde in fish could be done using two approaches: the diffusion rate approach (validation 75-100%) and the ratio of formaldehyde, TMA, and TMAO (validation 96,47%).Keywords: Formaldehyde, fishery product, food preservative, mathematical formalulation, Surida tumbil